Endowment of Bride-to-be’s Money (Urgency and Implementation) - Sujono, Imam; Natalia, Desti; Wahyuningsih, Arum Ayu; Ayu, Feni Sri (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
Money waqf for the bride and groom is a form of worship that can bring people closer to Allah SWT. In practice, money waqf for the bride and groom sets aside some of the assets in the form of money for the bride and groom before the wedding, which is then donated for public purposes or charity. This program is a collaborative campaign program between BSI, the Indonesian Waqf Board (BWI) and the Ministry of Religion. Waqf money for prospective brides and grooms has significant social and economic implications. What is interesting is the urgency and implementation of the waqf money for the bride and groom. This type of research uses field research and is supported by library research. This research uses descriptive analytical research methods with a qualitative approach. Data was collected through literature study, observation, and interviews with several sources related to money waqf for prospective brides and grooms. The research results show that the urgency of waqf money for the bride and groom lies in the social contributions and worship made by the bride and groom, as well as the benefits provided to society. Several obstacles in the field related to the implementation of money waqf for the bride and groom are something that is still understandable because the money waqf program for the bride and groom is still really new and needs adjustments from the KUA and the community. Of course, this program will continue to develop with evaluation of existing obstacles in the field. All parties are optimistic that this program will run well and bring many benefits.